2002
DOI: 10.4049/jimmunol.169.1.500
|View full text |Cite
|
Sign up to set email alerts
|

Skin Graft Rejection Elicited by β2-Microglobulin as a Minor Transplantation Antigen Involves Multiple Effector Pathways: Role of Fas-Fas Ligand Interactions and Th2-Dependent Graft Eosinophil Infiltrates

Abstract: β2-Microglobulin (β2m)-derived peptides are minor transplantation Ags in mice as β2m-positive skin grafts (β2m+/+) are rejected by genetically β2m-deficient recipient mice (β2m−/−). We studied the effector pathways responsible for the rejection induced by β2-microglobulin-derived minor transplantation Ags. The rejection of β2m+/+ skin grafts by naive β2m−/− mice was dependent on both CD4 and CD8 T cells as shown by administration of depleting mAbs. Experiments performed with β2m−/−CD8−/− double knockout mice g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…18 For example, IL-4-deficient mice have reduced transplant-associated eosinophilia and impaired T H 2 inflammation at the site of incompatible allograft transplants, suggesting that eosinophils may modulate the immune responses leading to transplant rejection. 19 In addition, both IL-4 and IL-13 are associated with tumor cell death in many types of cancer, 20 and our recent studies using eosinophil-specific antibodies have demonstrated that nearly all human and/or mouse cancers are associated with a robust eosinophil infiltrate at some point in tumor growth. 21 Thus, although further analyses are certainly needed, it is interesting to speculate that eosinophils may be a little recognized participant in the modulation of tumor-associated T H 2 immune responses (or alternatively the downregulation of tumor-associated cytotoxic T H 1 responses).…”
Section: Eosinophils: Regulators Of T H 2 Inflammatory Responsesmentioning
confidence: 97%
“…18 For example, IL-4-deficient mice have reduced transplant-associated eosinophilia and impaired T H 2 inflammation at the site of incompatible allograft transplants, suggesting that eosinophils may modulate the immune responses leading to transplant rejection. 19 In addition, both IL-4 and IL-13 are associated with tumor cell death in many types of cancer, 20 and our recent studies using eosinophil-specific antibodies have demonstrated that nearly all human and/or mouse cancers are associated with a robust eosinophil infiltrate at some point in tumor growth. 21 Thus, although further analyses are certainly needed, it is interesting to speculate that eosinophils may be a little recognized participant in the modulation of tumor-associated T H 2 immune responses (or alternatively the downregulation of tumor-associated cytotoxic T H 1 responses).…”
Section: Eosinophils: Regulators Of T H 2 Inflammatory Responsesmentioning
confidence: 97%
“…Skin grafts were prepared from tails of female mice and grafted onto the flanks of the recipients as previously described (1,10). Vaseline gauze was placed over the graft and sticking plaster was applied around the trunk.…”
Section: Skin Graftingmentioning
confidence: 99%
“…Untreated recipients rapidly reject fully allogeneic heart and skin grafts (10,11,22). In contrast, minor Ag-disparate transplants prime lower frequencies of effector T cells, often with the same proinflammatory phenotype as T cells induced to a fully allogeneic graft (7,10,17,22,25,26). Nonetheless, such minor Ag-disparate grafts are rejected at a slower pace than MHC-disparate grafts, and in some situations minor Ag-disparate transplants are not rejected at all (7,10,17).…”
mentioning
confidence: 96%